EFFECT OF DOUBLING THE ALTITUDE ON SERUM TESTOSTERONE LEVELS OF UNTRAINED YOUNG MALES SUBJECTED TO STANDARD EXERCISE - Badar, Ahmed; Yousuf, Muhammad; Sultan, Norin; Jan, Muhammad; Ahmed, Ayesha; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: The exercise has got a definite effect on serum testosterone level like many other physical and psychological stressors. Almost no study is available about the effects of standard exercise at two different altitudes in the same group of untrained exercisers. However, some data is available regarding trained athletes. This study was designed to compare the effect of doubling the altitude on serum testosterone level in the same group of untrained men exposed to standard exercise. Materials and Methods: 10 untrained male subjects were exposed to a standard exercise (submaximal cycle ergometer test) at 4300 feet and 8600 feet ASL (above sea level). Serum testosterone level was tested in the venous samples taken before and after the exercise. Results: The testosterone levels before the exercise were not significantly different at the two heights, however significant difference was observed in the samples taken immediately after exercise mid 2 hours after exercise. In both these cases serum testosterone at the higher altitude was significantly more. Conclusions: Standard exercise at high altitude in untrained men leads to an increase in testosterone level that is significantly more than a similar exercise at a lower altitude.